Caracterización de los procesos de reparación de los elementos exteriores de la carrocería fabricada en aluminio para vehículos premium (2018)
The development of the Project, it began by collecting the information of the most used materials in the bodies of Premium brands and which of these are manufactured in aluminum according to its segment, brand, version and significant representation in the market, subsequently the characteristics of the workshop were established, after each one of the necessary processes for the repair of the pieces was made and identified, defining their level of damage and materials with the necessary characteristics to work the aluminum sheet. Time was taken during the procedures to perform a cost analysis and see the feasibility of the project. It was made thanks to the experience and research background that Cesvi Colombia S.A has, this information was compiled to be attached in its entirety in a database.